МЕТОДИЧНІ РЕКОМЕНДАЦІЇ ЩОДО ОРГАНІЗАЦІЇ ТА ПРОВЕДЕННЯ ПРАКТИЧНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО ФАХІВЦЯ З ДОШКІЛЬНОЇ ОСВІТИ (Педагогіка вищої та середньої школи, 2008)
In the article under consideration the effective conditions of the practical training and developing of creative personality of future teachers who are present students of the pedagogical department are considered by the author.